Question

Find the general solution. Explain and show all steps.

[(e^t)y - t(e^t)] dt + [1 + (e^t)] dy = 0

Answer #1

Find the general solution to the following:
[(e^t)y-t(e^t)]dt+[1+(e^t)]dy=0

Find the general solution of the equation.
d^2y/dt^2-2t/(1+t^2)*dy/dt+{2/(1+t^2)}*y=1+t^2

Find the general solution to the given differential
equation. 1+(1+ty)e^ty+(1+t^2e^ty) dy/dt=0

find the general solution of the differential equation dy/dt -
2y = t^2 * e^2t

Find the general solution of the system
dx/dt = 2x + 3y
dy/dt = 5y
Determine the initial conditions x(0) and y(0) such that the
solutions x(t) and y(t) generates a straight line solution. That is
y(t) = Ax(t) for some constant A.

Are both of the following IVPs guaranteed a unique solution?
Explain. (a) dy/dt =y^ 1/3sin(t), y(π/2)=0. (b) dy/dt =y^1/3
sin(t), y(π/2)=4.

Consider the linear system
dY/dt=(0 2 −2 −1)Y
(a) Find the general solution.
(b) Find the particular solution with the initial value
Y0=(−1,1).

find the solution for the DE
dy/dt +ty^3 +y/t = 0
answer explicitly if passible

Find particular solution to the non-homogeneous linear system.
Explain and show all steps.
X' = [ 0 2 ] X + [ 1 ] (e^t)
[ -1 3 ] [ -1 ]

Solve the initial value problem
t^(13) (dy/dt) +2t^(12) y =t^25 with t>0 and y(1)=0
(y'-e^-t+4)/y=-4, y(0)=-1

ADVERTISEMENT

Get Answers For Free

Most questions answered within 1 hours.

ADVERTISEMENT

asked 6 minutes ago

asked 32 minutes ago

asked 40 minutes ago

asked 52 minutes ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 2 hours ago